Risk factors for nonunion of bone fracture in pediatric patients: An inception cohort study of 237, 033 fractures. Issue 31 (August 2018) - Zura, Robert; Kaste, Sue C.; Heffernan, Michael J.; Accousti, William K.; Gargiulo, Dominic; Wang, Zhe; Steen, R. Grant
Abstract : Abstract: Adult fracture nonunion risk is related to injury severity and surgical technique, yet nonunion is not fully explained by these risk factors alone; biological risk factors are also important. We test a hypothesis that risk factors associated with pediatric fracture nonunion are similar to adult nonunion risk factors. Inception cohort study in a large payer database of pediatric fracture patients (0–17 years) in the United States in calendar year 2011. Continuous enrollment in the database was required for 12 months, to allow time to capture a nonunion diagnosis. The final database collated demographic descriptors, treatment procedures as per Current Procedural Terminology (CPT) codes, comorbidities as per International Statistical Classification of Diseases and Related Health Problems (ICD-9) codes, and drug prescriptions as per National Drug Code Directory (Red Book) codes. Logistic regression was used to calculate odds ratios (ORs) for variables associated with nonunion. Among 237, 033 pediatric fractures in 18 bones, the nonunion rate was 0.85%. Increased nonunion risk was associated with increasing age, male gender, high body-mass index, severe fracture (e.g., open fracture, multiple fractures), and tobacco smoking (all, P < .0001). Nonunion rate varied with fracture location; scaphoid, neck of femur, and tibia/fibula were most likely to go to nonunion. Nonunion ORs were significantly increased for risk factors including; surgical procedure, cardiovascular disease, Vitamin D deficiency, osteoarthritis, osteoporosis, and opioid prescription (all, multivariable P < .001). Nonunion is rare in pediatric patients, but nonunion risk increases with increasing age. We confirm a hypothesis that risk factors for pediatric nonunion are similar to adult nonunion risk factors. Scaphoid fractures in adolescents have nearly the same risk of nonunion as in adults. Opioids should be used cautiously in pediatric patients, as they are associated with a significant and substantial elevation of nonunion risk. Level of Evidence: Prognostic study, Retrospective, Level II.